Hypertrophy in Skeletal Myotubes Induced by Junctophilin-2 Mutant, Y141H, Involves an Increase in Store-operated Ca(2+) Entry via Orai1 - Woo, Jin Seok (American Society for Biochemistry and Molecular Biology, 2012)
Junctophilins (JPs) play an important role in the formation of junctional membrane complexes (JMC) in striated muscle by physically linking the transverse-tubule and sarcoplasmic reticulum (SR) membranes. Researchers have found five JP2 mutants in humans with hypertrophic cardiomyopathy. Among these, Y141H and S165F are associated with severely altered Ca(2+) signaling in cardiomyocytes. We previously reported that S165F also induced both hypertrophy and altered intracellular Ca(2+) signaling in mouse skeletal myotubes. In the present study, we attempted to identify the dominant-negative role(s) of Y141H in primary mouse skeletal myotubes. Consistent with S165F, Y141H led to hypertrophy and altered Ca(2+) signaling (a decrease in the gain of excitation-contraction coupling and an increase in the resting level of myoplasmic Ca(2+)). However, unlike S165F, neither ryanodine receptor 1-mediated Ca(2+) release from the SR nor the phosphorylation of the mutated JP2 by protein kinase C was related to the altered Ca(2+) signaling by Y141H. Instead, abnormal JMC and increased SOCE via Orai1 were found, suggesting that the hypertrophy caused by Y141H progressed differently from S165F. Therefore JP2 can be linked to skeletal muscle hypertrophy via various Ca(2+) signaling pathways, and SOCE could be one of the causes of altered Ca(2+) signaling observed in muscle hypertrophy.